Advance care planning with chronically ill patients: A relational autonomy approach. (March 2020) - Killackey, Tieghan; Peter, Elizabeth; Maciver, Jane; Mohammed, Shan
Advance care planning is a process that encourages people to identify their values, to reflect upon the meanings and consequences of serious illness, to define goals and preferences for future medical treatment and care, and to discuss these goals with family and health-care providers. Advance care planning is especially important for those who are chronically ill, as patients and their families face a variety of complex healthcare decisions. Participating in advance care planning has been associated with improved outcomes; yet, despite over 25 years of public awareness campaigns, research, and interventions developed to increase participation, advance care planning completion rates for people with chronic illnesses are no different than those in the general public (approximately 25%). Advance care planning has traditionally used an individualistic approach to autonomy, which puts forward an understanding of agents as independent, rational and self-interested persons. Because this individualistic approach has been largely unsuccessful in improving advance care planning uptake, a re-examination of the philosophical underpinnings of this practice and an exploration of alternative frameworks is warranted. In offering this exploration, we briefly outline two current perspectives on autonomy: the individualistic view and the relational view as articulated by feminist philosophers. Using a critical examination of the theoretical and empirical work on this topic, we argue that the individualistic view of autonomy does not sufficiently capture the relational and social complexities of the decision-making process of advance care planning. To offer a counterpoint, we examine the relational view of autonomy and suggest that this perspective is better aligned with the process of advance care planning. Specifically, we demonstrate that a relational model of autonomy is well suited to exploring advance care planning for four main reasons: (1) it recognizes the importance of relationships, (2) it reflects the fluctuating nature of autonomy in chronic illness, (3) it recognizes vulnerability, and (4) it is consonant with empirical work examining the advance care planning process.